Development of an Activity Patterns Scale (APS) - Esteve-Zarazaga, Rosa; Ramírez-Maestre, María del Carmen; López-Martínez, Alicia Eva; Serrano-Ibáñez, Elena Rocío; Ruiz-Párraga, Gema Teresa; Morales, Ángelines; Peters, Madelon L. (My University, 2015)
Six activity patterns were identified across various self-report measures in participants with chronic pain: Pain Avoidance, Activity Avoidance; Task Contingent Persistence; Excessive Persistence, Pain Contingent Persistence and Pacing (Kindermans et al., 2011). It was proposed that instruments assessing “pacing” should include items addressing one specific pacing behavior (breaking tasks into smaller pieces; taking frequent short rests and speeding up or slowing down) with a single goal (increasing activity level, conserve energy for valued activities and pain reduction) (Nielson et al., 2013). The aim of the present study was to develop an instrument to assess the activity patterns identified by Kindermans et al. (2011). The instrument also included three pacing scales one for each of the aforementioned goals. Methods A sample of 229 patients with fibromyalgia and 62 suffering other rheumatic diseases answered online the APS and the “Patterns of Activity Measure-Pain” (POAM-P) (Cane et al., 2007). Three alternative factor structures were tested by confirmatory factor analyses performed via structural equation modelling. . Results The structure with the best fit had 8 factors corresponding to the hypothesized scales: Pain Avoidance (α=.60), Activity Avoidance (α=.60); Task Contingent Persistence (α=.81); Excessive Persistence (α=.84), Pain Contingent Persistence (α=.70), Pacing for increasing activity (α=.76), Pacing for energy conservation (α=.72) and Pacing for pain reduction (α=.65). The correlations with the POAM-P scales were high and in the postulated direction. Conclusions The APS showed adequate reliability and structural validity. According to these results, Avoidance, Persistence and Pacing seem to be multidimensional constructs.
Keywords: Dolor; Avoidance; Persistence; Patterns of activity; Scale